UNCOVERING THE EFFECTS OF GEOGRAPHICAL FACTORS ON VEGETATION DISTRIBUTION IN DISTRICT GUJRAT, PUNJAB, PAKISTAN - Syeda Saba Tassadduq; Shamim Akhtar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Vegetation distribution in any region is directly related to biotic and abiotic environmental factors. Present study aimed at recording the diversity patterns, richness and distribution of wild vegetation in relation to ecological gradients in the district Gujrat, Punjab, Pakistan during 2020 to 2022. For this, a randomized sample technique was applied across the district of Gujrat through GIS to record data on wild flora and linked it with environmental factors After evaluation of the IVI (importance value index), for each wild species along with the ecological data, the data were assessed via multivariate analysis (ordination and cluster analysis) performed by the use of R studio and Canoco software. In total, 119 plant species belonging to 36 families were identified. Reproductive phenological results showed that the maximum number of plant species reached the flowering stage during March-April (49 spp.) followed by August-September (40 spp.). The mean minimum temperature, wind speed, precipitation and soil moisture significantly differed (p-adj. <0.05), which is important for determining flowering phenological responses. To record vegetation, 90 elevational transects (grids 5×5 km2) containing 270 sampling stations were explored by using the raster vegetation sampler method. Soil features data was calculated from 90 selected plots by soil sampling in triplicates through handheld Global Positioning System (GPS). Canonical correspondence analysis revealed significant contributions of soil features. In 1st quadrat soil pH, in 2nd quadrat EC, moisture, and calcium carbonate, in 3rd quadrat soil saturation, and in 4th quadrat N, P, K and SOM were found to have a strong influence on vegetation in various microhabitats of research district. Findings of this research depicted that dynamics in phenology, topography and soil factors influence on diversity pattern of wild flora of district Gujrat significantly. The impact of these abiotic environmental challenges might impose the enduring challenge to wild vegetation of research district highlighted the requirement for making conservation efforts.